Rheumatoid Factor and Disease Activity Are Independent Predictors of Lymphoma in Primary Sjögren's Syndrome. Issue 4 (April 2016) - Nocturne, G.; Virone, A.; Ng, Wan‐Fai; Le Guern, V.; Hachulla, E.; Cornec, D.; Daien, C.; Vittecoq, O.; Bienvenu, B.; Marcelli, C.; Wendling, D.; Amoura, Z.; et al.
Abstract : Objective: To define parameters predictive of lymphoma development in patients with primary Sjögren's syndrome (SS). Methods: A multicenter case–control survey was performed to identify predictors of lymphoma. Cases were patients who developed lymphoma after diagnosis of primary SS and were mainly recruited through the Club Rhumatismes et Inflammation network. For each case, 2 controls (matched for disease duration and age) were randomly selected among patients with primary SS and without lymphoma. Cases and controls were compared using univariate analysis and then using multivariate analysis to identify independent predictors of lymphoma. Results: One hundred one patients with primary SS and lymphoma were included. Eighty‐seven patients were women (86.1%), and the mean ± SD age at lymphoma diagnosis was 57.4 ± 12.6 years. The most frequent histologic type was B cell non‐Hodgkin's lymphoma (NHL) in 99 of 101 patients, with marginal‐zone lymphoma in 76 of the 99 patients (76.8%) including 58 (58.6%) with lymphoma of the mucosa‐associated lymphoid tissue type. Lymphomas were most frequently located in the salivary glands (43 patients). A specific treatment was initiated at diagnosis in 87 patients with B cell NHL, and 61 patients (61.6%) achieved complete sustained remission after the first line of treatment. In the multivariate analysis, salivary gland enlargement, the presence of rheumatoid factor (RF), low C4, cryoglobulinemia, lymphopenia, and disease activity according to the European League Against Rheumatism Sjögren's Syndrome Disease Activity Index (excluding the lymphoma domain) were found to be predictors of lymphoma. No previous treatment for primary SS was associated with any effect on lymphoma occurrence. Conclusion: In addition to previously known factors predictive of lymphoma occurrence, the independent roles of RF and disease activity were demonstrated in this case–control study of primary SS–associated lymphoma. Our findings highlight the roles of chronic antigenic stimulation and disease activity in the development of this severe complication.